Search for Higgs boson decays to beyond-the-Standard-Model light bosons in four-lepton events with the ATLAS detector at √s=13 TeV - Santos, S. P. Amor dos (2018)
A search is conducted for a beyond-the-Standard-Model boson using events where a Higgs boson with mass 125 GeV decays to four leptons (ℓ = e or μ). This decay is presumed to occur via an intermediate state which contains one or two on-shell, promptly decaying bosons: H → ZX/XX → 4ℓ, where X is a new vector boson Zd or pseudoscalar a with mass between 1 and 60 GeV. The search uses pp collision data collected with the ATLAS detector at the LHC with an integrated luminosity of 36.1 fb−1 at a centre-of-mass energy s=13 TeV. No significant excess of events above Standard Model background predictions is observed; therefore, upper limits at 95% confidence level are set on modelindependent fiducial cross-sections, and on the Higgs boson decay branching ratios to vector and pseudoscalar bosons in two benchmark models.